2016
DOI: 10.1001/jamadermatol.2015.2038
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Orientation and Indoor Tanning Device Use

Abstract: should be analyzed because they may be more prevalent among sexual minority men 4 and associated with skin cancer risk behaviors. 5 Sexual orientation disparities in other skin cancerrelated behavioral risk factors should be further examined. 6 Gay and bisexual men reported not only significantly more indoor tanning than straight men but also rates comparable to women. Although previous efforts at curbing indoor tanning have focused on high-risk groups, such as young women, the large magnitude of disparities i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 4 publications
1
21
0
Order By: Relevance
“…Recent American investigations found that gay and bisexual men engage significantly more in indoor tanning practices than straight men and display prevalence of use comparable to women . The opposite association was found for homosexual women .…”
Section: Who Uses Sunbeds In Europementioning
confidence: 98%
“…Recent American investigations found that gay and bisexual men engage significantly more in indoor tanning practices than straight men and display prevalence of use comparable to women . The opposite association was found for homosexual women .…”
Section: Who Uses Sunbeds In Europementioning
confidence: 98%
“…45 Non-infectious diseases Skin cancer and indoor tanning-Skin cancer and indoor tanning might be more common among MSM. [46][47][48][49][50] In national and California surveys from 2001 to 2013, gay and bisexual men were twice as likely as heterosexual men to report having had non-melanoma skin cancers. 47 In those surveys, indoor tanning and frequent indoor tanning were 2 to 6 times more common among gay and bisexual men than heterosexual men.…”
Section: 40mentioning
confidence: 99%
“…One likely explanation for this disparity is that ultraviolet (UV) light exposure behaviors differ among SMM. As compared to heterosexual males, SMM report between three‐ to sixfold higher rates of indoor tanning, a known human carcinogen . This includes adolescent and young adult SMM, among whom indoor tanning is most associated with increased skin cancer risk .…”
Section: Tanning Behavior and Skin Cancer Riskmentioning
confidence: 99%
“…As compared to heterosexual males, SMM report between three‐ to sixfold higher rates of indoor tanning, a known human carcinogen . This includes adolescent and young adult SMM, among whom indoor tanning is most associated with increased skin cancer risk . SMM are also more likely to use sunless tanning products and less likely to wear protective clothing when outdoors, indicating an increased desire for tanned skin and, potentially, chronic sun exposure in this group …”
Section: Tanning Behavior and Skin Cancer Riskmentioning
confidence: 99%